Elevated levels of neutrophil gelatinase-associated lipocalin among OCD patients: an exploratory study - Raposo-Lima, Catarina (BMC Psychiatry, 2021)
BACKGROUND: Obsessive-compulsive disorder (OCD) is a debilitating psychiatric disease that is characterized by its clinical heterogeneity and complex pathophysiology. This complexity comes from the diversity of pathophysiological factors that have been proposed to be involved in the natural history of the disorder. Many theories on OCD pathology support inflammation as a pathophysiological factor, although studies are not consistent on the presence of a pro-inflammatory state among OCD patients. However, some pre-clinical animal studies suggest lipocalin-2 (LCN2), an analogous form of the acute-phase pro-inflammatory protein neutrophil gelatinase-associated lipocalin (NGAL), may be involved in in the regulation of the stress response, which is thought to be disrupted in OCD. METHODS: Twenty-one OCD patients and 19 healthy subjects participated in this exploratory study. Levels of NGAL were assessed in the peripherous blood of all participants. Severity of disease was assessed using the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS). RESULTS: OCD patients exhibited significantly higher levels of NGAL when compared to healthy control subjects. No correlation was found between elevated levels of NGAL and severity of symptoms. CONCLUSIONS: This is the first study to report elevated levels of NGAL among OCD patients, adding evidence for a possible role of immune dysregulation in the pathophysiology of OCD.